Making parents : the ontological choreography of reproductive technologies - Thompson, Charis (Inside technology., 2005)
"Assisted reproductive technology (ART) makes babies and parents at once. Drawing on science and technology studies, feminist theory, and historical and ethnographic analyses of ART clinics, Charis Thompson explores the intertwining of biological reproduction with the personal, political, and technological meanings of reproduction. She analyzes the "ontological choreography" at ART clinics - the dynamics by which technical, scientific, kinship, gender, emotional, legal, political, financial, and other matters are coordinated - using ethnographic data to address questions usually treated in the abstract